Pengaruh Metode Bermain dengan Bahan Bekas Terhadap Kemampuan Berhitung Anak Kelompok B 5-6 Tahun - Ayu Ratna Pratiwi; Siti Fadjryana Fitroh; Dwi Nurhayati Adhani (Universitas Trunojoyo Madura, 2018)
The purpose of the research is to know whether there is a significant influence of the method of playing with the used materials on the ability of counting children in group B (age 5-6 years) in Kindergarten Development Glagah Lamongan. This research uses quantitative approach by using experimental method with Preexperimental research design One-group pre-test post-test type. Number of samples of 15 children in group B Kindergarten Development Glagah Lamongan. Data collection techniques in this study through participant observation and documentation in the form of photos of activities and plans of daily learning. Demonstrate large data processing using Wilcoxon marked test data analysis. The result of data analysis obtained by TcountTtable (0 25) and Ha value received. Indicates that there was an increase in pretest of 27.5% to the time of posttest 43.49% Based on the data analysis there was a significant influence between the method of playing with used materials on the ability of counting children.